Generation Z and volunteering: A national culture perspective - J. Perić; M. Leko Šimić; M. V. Pevnaya; E. Sharma (Obrazovanie i Nauka)
Introduction. Volunteering in the modern world is one of the basic resources for solving society’s problems, an activity that helps students in different countries to build personal and professional competencies. The limited research that makes it possible to analyse the cross-cultural elements of student volunteering has led to a scientific interest in the problem of matching the cultural context and volunteer activities of students from universities in India, Russia and Croatia. The new research perspective covered the perception of volunteering, the behaviour of Generation Z, to which the students of the three countries under consideration belong, as well as the significance of the peculiarities of national culture for the volunteering activity of university youth.The aim of this study is to assess the national cultural context and the level of its significance for the perception of volunteering, motivation and the experience of volunteering of students of management specialties at universities in India, Russia and Croatia.Methodology and research methods. Comparative sociological research is implemented based on the theory of generations, Hofstede’s theory of cultural dimensions and the cultural factors of the macro level defined by him. The study involved students from regional universities in three countries: India, Russia and Croatia. The main method for collecting primary data was questionnaire survey. The questionnaire consisted of several blocks of questions, which allowed assessing the subjective perception of volunteering by students, their personal experience and motivation for volunteering, demographic characteristics of the respondents. The total sample was 943 people; the average age of the respondents was 21 years. Students participated anonymously on a voluntary basis, without any incentives. A one-way analysis of variance, the Leuven test, was used to analyse the data. The collected data was processed using the IBM SPSS Statistics 23.0 program.Results and scientific novelty. The results of the study showed that, in general, Generation Z actually has certain specific characteristics regarding volunteering and volunteering, while these characteristics do not depend on the national culture of a particular state. On the basis of the respondents’ answers, the factors influencing students’ volunteering were identified. Thus, the results of the study proved that the motivation of students for volunteering in the present and in the future does not differ significantly in the compared countries. The study results also did not demonstrate differences in the importance of utilitarian and altruistic motives for volunteering students from different countries. It was found that university students in India are more motivated to volunteer due to utilitarian motives; they are more likely to volunteer in comparison with students from Russia and Croatia. The level of uncertainty avoidance by students, personal benefits from volunteering, and their perception of the value of volunteering in general were measured. The authors provide an overview of the development of volunteering in the three compared countries, defining the social and cultural context in them.Practical significance. The conducted research in the context of popularisation of volunteering as a direction of practice-oriented education at universities in different countries enriches the field of knowledge about student volunteering and its cross-cultural elements.The results of this work can be useful both for universities in the implementation of the “third mission” for the development of the local community, and for all those involved in the promotion of volunteer activities and recruitment volunteering both locally, nationally and internationally with the aim of more engaging Generation Z in the volunteer movement.